The Effect of Intellectual Capital on the Timeliness of Submission of Banking Financial Reports in Indonesia - Arif Rochman; Bandi Bandi; Probohudono Agung Nur; Djuminah Djuminah (Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to examine the influence of intellectual capital consisting of (human capital, structural capital and relational capital) on the timeliness of financial reporting of banks in Indonesia. The sample in this study was 42 banks listed on the Indonesia Stock Exchange. The data analysis method in this study used the STATA application. The results of this study indicate that human capital (HCE) has a positive effect on the timeliness of financial reporting, while structural capital (SCE) and relational capital (RCE) do not affect the timeliness of financial reporting.